2003
DOI: 10.1111/j.1945-5100.2003.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the source regions of martian meteorites using MGS TES: Integrating martian meteorites into the global distribution of igneous materials on Mars

Abstract: Abstract-The objective of this study was to identify and map possible source regions for all 5 known martian meteorite lithologies (basalt, lherzolite, clinopyroxenite, orthopyroxenite, and dunite) using data from the Mars Global Surveyor Thermal Emission Spectrometer (MGS TES). We deconvolved the TES data set using laboratory spectra of 6 martian meteorites (Los Angeles, Zagami, ALH A77005, Nakhla, ALH 84001, and Chassigny) as end members, along with atmospheric and surface spectra previously derived from TES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
166
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(179 citation statements)
references
References 65 publications
12
166
1
Order By: Relevance
“…Mineral compositions on Mars range from intermediate to ferroan olivine and intermediate to calcic plagioclase (Bandfield, 2002;McSween et al, 2004). Both high and low Ca pyroxenes have been detected (Mustard et al, 1997;Hamilton et al, 2003;Bibring et al, 2005;McSween et al, 2006). Glass of a basaltic andesite composition, documented in a Martian meteorite (Greshake et al, 2004), would dissolve only slightly more slowly than the basalt glass dissolution line on Figure 2.…”
Section: Mineral Persistencementioning
confidence: 99%
“…Mineral compositions on Mars range from intermediate to ferroan olivine and intermediate to calcic plagioclase (Bandfield, 2002;McSween et al, 2004). Both high and low Ca pyroxenes have been detected (Mustard et al, 1997;Hamilton et al, 2003;Bibring et al, 2005;McSween et al, 2006). Glass of a basaltic andesite composition, documented in a Martian meteorite (Greshake et al, 2004), would dissolve only slightly more slowly than the basalt glass dissolution line on Figure 2.…”
Section: Mineral Persistencementioning
confidence: 99%
“…The basaltic and andesitic-like signatures dominate the surface of Mars with only relatively minor olivine-rich or haematite-rich areas. However, Hamilton et al (2000Hamilton et al ( , 2003 and Bibring & Erard (2001) noted that the basaltic TES spectra do not closely match those of the shergottites. Furthermore, Wyatt & McSween (2002) and Wyatt et al (2004) modified the deconvolution mineralogy, significantly decreasing the estimated feldspar in both terrane types.…”
Section: Source Regions and The Martian Surfacementioning
confidence: 99%
“…Peridotitic shergottites may have crystallized in situ as plutonic or intrusive material at deeper crustal levels. Hamilton et al (2003) reported the results of a search using TES data for spectral signatures close to those of the SNC types. Although some olivine-and orthopyroxene-rich areas were identified, no fits to the laboratory SNC spectra were found.…”
Section: Source Regions and The Martian Surfacementioning
confidence: 99%
“…13). This spectrally diverse area of Mars has been mapped in detail using previously available orbital spectral and visible datasets, and has become well known for both its mafic (Hamilton et al, 2003;Hoefen et al, 2003;Hamilton and Christensen, 2005;Tornabene et al, 2008) and hydrated silicate mineral diversity (Mangold et al, Table 3 Laboratory mineral spectra used in study. See Fig.…”
Section: Comparison With Crism Datamentioning
confidence: 99%